2002
DOI: 10.1046/j.1523-5378.2002.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of CDX2 in the Gastric Mucosa With and Without Intestinal Metaplasia: Effect of Eradication of Helicobacter pylori

Abstract: Our results indicate that CDX2 expression in the gastric mucosa is found in patients with chronic gastritis and is closely associated with IM. CDX2 expression in IM or the gastric epithelial cells did not disappear after eradication of H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 26 publications
6
62
1
3
Order By: Relevance
“…7,13,[15][16][17][18]30 Our results are entirely consistent with these studies in that CDX2 staining was observed in only a subset of gastric cancers and significantly favored the intestinal-type tumors over the diffuse variants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…7,13,[15][16][17][18]30 Our results are entirely consistent with these studies in that CDX2 staining was observed in only a subset of gastric cancers and significantly favored the intestinal-type tumors over the diffuse variants.…”
Section: Discussionsupporting
confidence: 91%
“…11,12 In humans, intestinal metaplasia of the stomach and esophagus is consistently accompanied by CDX2 expression. 6,[13][14][15][16] The relationship between CDX2 expression and intestinal differentiation suggests that CDX2 may serve as a specific marker for epithelial neoplasms of the gastrointestinal (GI) tract. This is supported by several recently published surveys in which selective staining of colorectal and duodenal adenocarcinomas has been observed using a commercially available monoclonal antibody to CDX2.…”
mentioning
confidence: 99%
“…24,35 The involvement of TLR2 and/or TLR4 in Helicobacter pylori infections has been revealed in cultured gastric epithelial cell lines, 33,34 in which MUC2 was induced to express by TLR2/ bacterial components and the activation of NF-kB. 3,31,32 PAMPs-induced CDX2 and MUC2 overexpression via an NF-kB pathway located downstream of TLRs. This study showed that pretreatment of BECs with MG132 reduced the CDX2 and MUC2 mRNA upregulation induced by LPS, suggesting that upregulation of the CDX2 and MUC2 pathway by PAMPs was related to the activation of TLR2/ TLR4 with the translocation of NF-kB.…”
Section: Intestinal Metaplasia Of Bile Ducts H Ikeda Et Almentioning
confidence: 99%
“…Sixteen types of MUC have been identified. Intestinal metaplasia associated with the aberrant expression of MUC2 [1][2][3][4] is reportedly involved in tumorigenesis in several organs. Recent studies revealed that CDX2, a caudalrelated homeobox gene encoding an intestine-specific transcription factor, is a regulatory factor of intestinal development and expression of intestinal genes including MUC2 and is involved in intestinal metaplasia.…”
mentioning
confidence: 99%
“…In two separate mouse models, ectopic expression of CDX2 in the stomach induced gastric intestinal metaplasia Silberg et al, 2002). In humans, CDX2 is not expressed in normal gastric cells but is prominently expressed in gastric intestinal metaplasia, consistent with its putative role in the induction of gastric intestinal metaplasia (Bai et al, 2002;Eda et al, 2002;Satoh et al, 2002;Almeida et al, 2003;Mizoshita et al, 2004b;Tsukamoto et al, 2004).…”
Section: Introductionmentioning
confidence: 83%